Investigation of Stress Effect on Shape Memory Alloys - Canbay, Canan Aksu; Ozkul, Iskender; Kalay, Ece (Amer Inst Physics, 2019)
The materials which perform the desired reactions are received from external influences such as temperature, pressure and magnetic field are called smart materials. Shape memory alloys, which are smart materials, show shape memory effect by solid-state phase transformation. With these properties, they are separated from the classical material groups. However, environmental factors affect the structure of shape memory alloys as like all materials. Furthermore, materials can age by temperatures shift, moisture, radiation, high strains, stress, etc. So that's the major reason of the materials deterioration rate increase. The purpose of using material will be lost day by day andtake them it a useless application. Therefore, in our study, the effect of the pressure applied to NiTi based shape memory alloy at different waiting periods and different applied pressures on phase transformation temperatures were investigated.
35th International Physics Congress of the Turkish-Physical-Society (TPS) -- SEP 04-08, 2019 -- Bodrum, TURKEY
Keywords: Model